2014
DOI: 10.1113/expphysiol.2014.079335
|View full text |Cite
|
Sign up to set email alerts
|

AGTR2 gene polymorphism is associated with muscle fibre composition, athletic status and aerobic performance

Abstract: New Findings r What is the central question of this study?Variations in genes are considered to be molecular determinants maintaining the expression of the slow or fast myosin heavy chains of adult skeletal muscle. The role of polymorphisms of candidate genes involved in skeletal muscle development, energy homeostasis and thyroid and calcium metabolism in the determination of muscle fibre type has not previously been reported. r What is the main finding and its importance?We show that the AGTR2 rs11091046 C al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 50 publications
0
32
1
Order By: Relevance
“…Alphaactinin-3 gene (ACTN3), peroxisome proliferator-activated receptor alpha gene, angiotensin II type 2 receptor gene, and angiotensin-converting enzyme gene polymorphisms have been reported to be associated with muscle fiber composition. [50][51][52][53] Moreover, polymorphisms in ACTN3, the product of which is a major component of Z-disks in fast-twitch muscle fibers 9 and the myostatin gene, the product of which suppress muscle growth, 54 explained the individual differences in muscle strength-related phenotypes. However, it remains unclear to what extent over 20 polymorphisms that have been reported to be related to muscle strength [55][56][57] explain the H 2 -msp.…”
Section: Discussionmentioning
confidence: 99%
“…Alphaactinin-3 gene (ACTN3), peroxisome proliferator-activated receptor alpha gene, angiotensin II type 2 receptor gene, and angiotensin-converting enzyme gene polymorphisms have been reported to be associated with muscle fiber composition. [50][51][52][53] Moreover, polymorphisms in ACTN3, the product of which is a major component of Z-disks in fast-twitch muscle fibers 9 and the myostatin gene, the product of which suppress muscle growth, 54 explained the individual differences in muscle strength-related phenotypes. However, it remains unclear to what extent over 20 polymorphisms that have been reported to be related to muscle strength [55][56][57] explain the H 2 -msp.…”
Section: Discussionmentioning
confidence: 99%
“…The C3123A (also known as rs11091046 or C4599A) polymorphism of the AGTR2 gene located within the 3-UTR of exon 3 has been reported to be associated with several cardiovascular phenotypes. By studying 2178 athletes from Russia and Poland, Mustafina et al [4] found that rs11091046 C allele carriers of the AGTR2 gene had a significantly higher percentage of slow-twitch fibers than A allele carriers [54.2 (11.1)% vs. 45.2 (10.2)%; P ¼ 0.003] in the group of 55 physically active, healthy men. The frequency of the AGTR2 C allele was significantly higher in male and female endurance athletes compared with power athletes (males: 62.7% vs. 51.7%; P ¼ 0.0038; females: 56.6% vs. 48.1%; P ¼ 0.0169) and control subjects (males: 62.7% vs. 51.0%; P ¼ 0.0006; elite female athletes: 65.1% vs. 55.2%; P ¼ 0.0488).…”
Section: Agtr2 Rs11091046 C Allelementioning
confidence: 97%
“…Cross-sectional association studies are another type of study design in sports genomics and examine whether athletes with one genotype (or allele) of a particular DNA sequence show different measures of a trait (e.g., VO 2max , strength measures, percentage of fast-twitch muscle fibers, cardiac size, lactate, etc.) compared to the rest of the sample [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies have been performed primarily in healthy adults (physically active college students, moderately trained and recreationally active subjects) and not high-level athletes; although not universally confirmed, athletes with more extensive training backgrounds may have distinct phenotypes [79-81] and genotypes than normally active subjects [82]. Moreover, to the authors’ best knowledge, there is no research concerning how the distinct genotypes that can be found within a high-level group of athletes [82-84] may influence the individual responses to concurrent training.…”
Section: Interference Between Concurrent Strength and Endurance Trainingmentioning
confidence: 99%